Translating the Most used MediaWiki messages: Success stories and improvements - Shahadu, Sadik; Aharoni, Amir E.; Akau, Kambai; Bobai, Zwandien (Septentrio Conference Series, 2021)
One of the conditions to create the first Wikimedia wiki in a new language is 100% translation of the "Most important" MediaWiki messages (also known as "Most used"). Some language communities struggle to complete this condition, but some succeed. This presentation will show: Why is this translation important in the first place. Recent completions of the Most important messages the Dagbani, Tyap, and some other languages: What different things did the translators do to achieve this. What has been done recently to make completing this task easier for everyone. What big new things can and should be done in the future to make it even more convenient and relevant.